2022
DOI: 10.1038/s41598-022-05740-8
|View full text |Cite
|
Sign up to set email alerts
|

Insights from density functional theory calculations on heteroatom P-doped ZnIn2S4 bilayer nanosheets with atomic-level charge steering for photocatalytic water splitting

Abstract: ZnIn2S4 (ZIS) is an efficient photocatalyst for solar hydrogen (H2) generation from water splitting owing to its suitable band gap, excellent photocatalytic behaviour and high stability. Nevertheless, modifications are still necessary to further enhance the photocatalytic performance of ZIS for practical applications. This has led to our interest in exploring phosphorus doping on ZIS for photocatalytic water splitting, which has not been studied till date. Herein, phosphorus-doped ZnIn2S4 (P-ZIS) was modelled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 60 publications
(68 reference statements)
0
7
0
Order By: Relevance
“…It is evident that ZIS has a direct bandgap at the Γ point whereas SnS has an indirect bandgap, which are consistent with previous studies. 61,62 Of note, the direct bandgap nature of ZIS is beneficial to enhance the light–matter interactions while the indirect bandgap nature of SnS contributes to extend the excess carrier lifetime. The synergy of them is conducive to improving the device performance.…”
Section: Resultsmentioning
confidence: 99%
“…It is evident that ZIS has a direct bandgap at the Γ point whereas SnS has an indirect bandgap, which are consistent with previous studies. 61,62 Of note, the direct bandgap nature of ZIS is beneficial to enhance the light–matter interactions while the indirect bandgap nature of SnS contributes to extend the excess carrier lifetime. The synergy of them is conducive to improving the device performance.…”
Section: Resultsmentioning
confidence: 99%
“…12,13 Besides, the photoelectric conversion efficiency of single-junction solar cells is limited by the Shockley–Queisser (SQ) model, 14,15 whose maximum conversion efficiency is about 33%. 3,14 ZnIn 2 S 4 (ZIS) is a kind of direct bandgap semiconductor with a bandgap of 2.34 eV, 16 with enormous potential applications in many fields such as charge storage, 17 thermoelectricity, 18 lithium batteries, 19 photocatalysis, 20–29 and solar cell. 30–33 In 2003, Lei et al first reported photocatalytic hydrogen evolution using ZIS.…”
Section: Introductionmentioning
confidence: 99%
“…20 After that Yang et al found that doping oxygen in ZIS can increase the average lifetime of the photo-induced electrons by 1.53 times, which is a strong evidence of carrier separation. 21 The non-metallic nitrogen 22 and sulfur doping 23 also can provide more reducing photo-generated electrons and lead to high photocatalytic activity. Besides, silver ion interstitial and doping in ZIS introduced acceptor state and donor state, respectively, which greatly increased the carrier density and charge transfer efficiency, thus enhancing the activity of the photocatalytic hydrogen evolution.…”
Section: Introductionmentioning
confidence: 99%
“…With a small band gap of ∼2.4 eV, the ternary sulfide ZnIn 2 S 4 is among the most promising visible-light-responsive photocatalytic materials. , However, the fast recombination of photoinduced carriers and the severe photocorrosion restrict its photocatalytic performance. To promote the charge transfer in ZnIn 2 S 4 , it is a feasible strategy to recombine it with TiO 2 with a high surface chemical activity. , Besides, it has been reported that a certain amount of sulfur vacancies can be generated in sulfides by calcination .…”
Section: Introductionmentioning
confidence: 99%